Microemulsion and liquid cristals as drug delivery systems (Revista Brasileira de Ciências Farmacêuticas, 2005)
Depending on the proportions, the mixture of surfactants with water, in the presence or absence of oil, may form different types of supramolecular aggregates. Among these, polymorphic structures represented by microemulsions (ME) and lyotropic mesophases-liquid crystals (LC), closely related with the nature and the proportion of the constituents, can exist. In this work, the role of these systems in the incorporation of drugs with different physico-chemical properties, influencing strongly the drug release as well as the bioavailability of the drugs, was discussed. Aspects about the formation and the characterization of ME and LC were also discussed. The analysis of the literature indicate that depending on the drug polarity the effect of ME or LC can be used to optimizes therapeutic effects through the control of rates and the drug release mechanisms.